Government Responses to International Refugees and Emerging Global Threat: Insights from Türkiye and Indonesia (Resolusi: Jurnal Sosial Politik, 2025)
This article examines how Türkiye and Indonesia, as emerging powers with distinct geopolitical roles, respond to the global refugee crisis through a comparative lens informed by Migration Transition Theory and Securitization Theory. Türkiye’s transformation into a major refugee-receiving country following the Syrian conflict has been accompanied by regulatory and integration-oriented policies, yet their implementation remains uneven at the local level. By contrast, Indonesia, despite its non-signatory status to the 1951 Refugee Convention, has evolved into a key transit and host context, relying primarily on humanitarian approaches and cooperation with international organizations. Using qualitative content analysis and thematic coding of secondary sources, this study identifies five central patterns shaping refugee governance: securitization of refugees, ad hoc humanitarian responses, labor market integration of refugees, socio-economic burdens on host communities, and coordination with international organizations. The findings indicate that Türkiye’s relatively institutionalized framework is constrained by resource disparities and administrative fragmentation, while Indonesia exhibits a hybrid governance model that balances humanitarian commitments with security considerations. Overall, the article highlights the adaptive yet fragmented character of refugee governance in the Global South and underscores persistent policy dilemmas between humanitarianism, sovereignty, and security in non-Western refugee-receiving states.